O ensino do trombone em cursos de música: reflexões a partir da teoria histórico-cultural - Teixeira, Alexandre (2024)
This thesis, linked to the Research Line on Theories of Education and Pedagogical Processes of the Graduate Program in Education at PUC Goiás, falls within the field of music education and aims to provide reflections on trombone teaching from the perspective of Vygotsky's Cultural-Historical Theory. It is based on the premise that this theory offers alternatives to the historical challenges of trombone teaching, particularly regarding the overcoming of traditional and technicist approaches, emphasizing the formation of scientific concepts, aesthetic experiences, and the development of creativity. With this understanding, the central problem investigated was: what contributions can the Cultural-Historical Theory offer to trombone teaching, considering qualitative transformations that foster the development of students' sensitivity and creativity? To answer this question, Vygotsky's Cultural-Historical Theory was sought as a theoretical foundation capable of supporting the proposed reflections. The specific objectives included: understanding, in a processual manner, the trajectory of art/music education in Brazil, with an emphasis on trombone teaching; identifying, through the study of scientific literature, the main theoretical approaches and problems related to the teaching of this instrument; and demonstrating the importance of the articulation between music education and Cultural-Historical Psychology for the construction of a methodology that promotes the integral development of students. The results show that the CulturalHistorical Theory constitutes a solid framework for driving methodological changes in trombone teaching, highlighting the role of the teacher as a mediator in the process of internalizing musical concepts and developing creativity. The research points out that trombone teaching, from this perspective, should go beyond the mere transmission of techniques, providing experiences that integrate emotion, sensitivity, and artistic expression. Thus, the main contribution of this study lies in offering pedagogical reflections that broaden the understanding of trombone teaching as a process of human formation, in which the construction of cultural and artistic meanings plays an essential role in the integral development of students